Polifunctionality of advertising clichés in modern media communications (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the questions of the functioning of advertising cliché in modern mass media discourse.
Keywords: advertising cliché; advertising text; functional characteristics